2002
DOI: 10.1002/art.10226
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proximal finger joint inflammation in patients with rheumatoid arthritis, using a novel laser‐based imaging technique

Abstract: Objective. To evaluate a newly developed laserbased imaging technique for the study of soft tissue changes and acute inflammatory processes of the proximal interphalangeal (PIP) joints in patients with rheumatoid arthritis (RA).Methods. A novel imaging device was developed which allows the transillumination of PIP joints using laser light in the near-infrared wavelength range. In a first clinical followup study, a total of 72 PIP joints of 22 patients with RA and 64 PIP joints of 8 healthy controls were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 14 publications
0
44
0
Order By: Relevance
“…Scheel et al [9] demonstrated that laser transillumination of finger joints can be useful as a sensitive follow-up analysis of joint inflammation. A neural network was employed for the classification of the one-dimensional scattering distributions, see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheel et al [9] demonstrated that laser transillumination of finger joints can be useful as a sensitive follow-up analysis of joint inflammation. A neural network was employed for the classification of the one-dimensional scattering distributions, see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The small geometry of the joints supports the application of this non-invasive method of examination [4,7,8]. A first clinical study [9] showed that laser transillumination of finger joints could be useful as a sensitive follow-up analysis of joint inflammation when complemented with an adequate image processing. For that purpose a new image segmentation algorithm [10] based on a non-local phase separation model is proposed.…”
Section: Introductionmentioning
confidence: 97%
“…This is why a so-called ''functional imaging procedure'' using for example MRT, is recommended as a complementary procedure to radiography. The comparatively low-cost optical diagnostics procedure would offer an interesting alternative, particularly as it has already proven successful in the first two studies [14,15].…”
Section: Article In Pressmentioning
confidence: 99%
“…Besides expensive tomographic approaches a robust procedure has become established in optical diagnostics of rheumatism: the PIP joint to be examined is transilluminated using a (laser diode or LED) point source and the scattered light image is plotted by a CCD camera [6][7][8]. Monte-Carlo simulations confirm the experimental outcome [9].…”
Section: Introductionmentioning
confidence: 99%